Intervenção fisioterapêutica para crianças com paralisia cerebral classificadas nos níveis IV e V do Sistema de Classificação da Função Motora Grossa (GMFCS): uma revisão de literatura - Vanessa Oliveira de Faria (2022)
Objective: to perform a literature review on physical therapy interventions for children with CP classified in levels IV and V of the GMFCS, in order to summarize the available evidence and assist health professionals in the application of research results in clinical practice. Methods: Electronic database search in Portuguese and English, without date restriction. Sample characteristics, type of intervention and results were extracted. The GRADE assessment tool was used to classify the evidence. Results: Eleven studies were included. Gait training on treadmill with body weight support was the most common intervention, followed by training on adapted bicycle ergometer, intensive therapy, horse therapy, postural management, electrical stimulation and music therapy. Regarding the GRADE classification two studies were classified as moderate, one as low and seven as very low. Conclusion: Few studies of moderate to low methodological quality were found that documented the effect of physical therapy interventions for children with CP with moderate to severe motor impairment.